2011
DOI: 10.1177/1545109710393308
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Options, Other Nonchemoprophylactic Factors, and Mother-to-Child Transmission of HIV in Zambia

Abstract: Background: The role of antiretroviral drugs in the prevention of mother-to-child transmission (PMTCT) of HIV is well known. The objective of this study is to explore how nonchemoprophylactic factors, including infant feeding practices, mother's HIV status disclosure, mode and place of delivery, infant gender, and maternal age, are related to MTCT. Methods: The study analyzed program data of DNA polymerase chain reaction (PCR) results from dried blood spot samples and selected client information from perinatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
9
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
7
9
1
Order By: Relevance
“…Our finding is comparable to those in many other publications [11], [12], [13], [14]. We had a similar finding when we previously analyzed a smaller subset of the same data presented here [6], [7].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding is comparable to those in many other publications [11], [12], [13], [14]. We had a similar finding when we previously analyzed a smaller subset of the same data presented here [6], [7].…”
Section: Discussionsupporting
confidence: 93%
“…Children lived from the five provinces supported by ZPCT – Central, Copperbelt, Luapula, North-Western, and Northern Provinces – between September 2007 and July 2010. This study is an update of an earlier analysis which covered the period between September 2007 and January 2009 [6], [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 80 infants aged 6 months or less, 40(50%) were exclusively breastfed, 30(37.5%) replacement feeding (received formula) and 10(12.5%) received mixed feeding. Similar to our findings, Anoje et al [55] from southern Nigeria reported high prevalence of 80% exclusive breast-feeding and Torpey [46] in Zambia reported 84% of babies receiving exclusive breast milk as compared with other feeding option. Our study showed that the risk of vertical transmission of HIV associated with exclusive breast feeding was considerably lower reported as 3(1.9%) compared with 4(2.5%) in replacement feeding and 8(5.0%) in mixed feeding.…”
Section: Discussionsupporting
confidence: 91%
“…The association was significant in the age groups six weeks to six months and six months to 12 months. They believe that place of delivery, disclosure of HIV positive status, and mother's age -do influence adherence to ARVs regimen, infant feeding practices, or counseling offered during PMTCT interventions [46]. In this present study, male had high frequency of 87(54.4% ) with prevalence of 52 (32.3%) in age group 0-3 months compared to 46(28.7%) female in the same age group which is similar to previous studies reported 88 males and 75 females with male to female ratio of 1.2:1 by Onankpa and Tahir et al [47], 121(54.0%) males (M), 103(46.0%) females (F) with an M: F ratio of 1:0.9 reported by Anígilájé et al [48], 63 (56.2%) male and 49(43.8%) female as reported by Jean [49] and 329(54.8%) males and 271(45.2%) females, giving a male: female ratio of 1.2:1 by Babatunde et al [50].…”
Section: Discussionmentioning
confidence: 99%